(untitled) (Papeles, 2016)
This paper presents research on the relationship between the knowledge of contraceptive methods thbarrinformational role of the school, being public or private. This analysis included a population of 192 teenagers (15 to 18 years old) from six schools. A survey was applied in which questions related to theoretical knowledge about contraceptive methods and socio-economic and cultural variables are answered.